1999
DOI: 10.1177/104345429901600302
|View full text |Cite
|
Sign up to set email alerts
|

Providing Quality Care in Childhood Cancer Survivorship: Learning From the Past, Looking to the Future

Abstract: As we move into the 21st century, we are faced with an increasing number of childhood cancer survivors who are living into their middle adult years and beyond. Providing appropriate, comprehensive follow-up care is a challenge for health care providers and one that can be met by developing quality follow-up programs for all childhood cancer survivors. The focus of these programs should be to educate these survivors on strategies to maximize their health and well being. This article discusses the evolution of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Evidence‐based and expert consensus guidelines exist for monitoring late toxicities in childhood cancer survivors into young adulthood and beyond . Specialized survivorship care includes the development of survivorship care plans and multidisciplinary coordination of care between pediatric and adult medicine subspecialists . One survivorship program reported that 34% of patients had a new health condition identified at initial screening based on guidelines, emphasizing the potential benefits of survivorship‐based health care .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence‐based and expert consensus guidelines exist for monitoring late toxicities in childhood cancer survivors into young adulthood and beyond . Specialized survivorship care includes the development of survivorship care plans and multidisciplinary coordination of care between pediatric and adult medicine subspecialists . One survivorship program reported that 34% of patients had a new health condition identified at initial screening based on guidelines, emphasizing the potential benefits of survivorship‐based health care .…”
Section: Discussionmentioning
confidence: 99%
“…Education about diagnosis, treatment, potential late effects, fertility-preserving options and sexual functioning should also become part of their health care. The development of patient education materials and individual, couple or group counseling are adequate in this context [5,23,64,66,68,129].…”
Section: Intervention With Patients and Families Prevent And Treat Sementioning
confidence: 99%
“…Representative articles published from the 1990s to the present have articulated the need for transitional care for childhood cancer survivors. [31][32][33][34] In 2002, the Children's Oncology Group (COG) established the Survivorship Transition Task Part of the rationale for health care transition is based on the major differences between adult-focused versus child-centered care. Adult care relies more consistently on patient initiative and has the potential to be more collaborative and empowering rather than predominantly nurturing and prescriptive.…”
Section: General Considerationsmentioning
confidence: 99%